Relating form to function in the hummingbird feeding apparatus - Alejandro Rico-Guevara (PeerJ, 2017)
A complete understanding of the feeding structures is fundamental in order to study how animals survive. Some birds use long and protrusible tongues as the main tool to collect their central caloric source (e.g., woodpeckers and nectarivores). Hummingbirds are the oldest and most diverse clade of nectarivorous vertebrates, being a perfect subject to study tongue specializations. Their tongue functions to intraorally transport arthropods through their long bills and enables them to exploit the nectarivorous niche by collecting small amounts of liquid, therefore it is of vital importance to study its anatomy and structure at various scales. I focused on the portions of the hummingbird tongue that have been shown to be key for understanding their feeding mechanisms. I used histology, transmission and scanning electron microscopy, microCT, and ex-vivo experiments in order to advance the comprehension of the morphology and functioning of the hummingbird feeding apparatus. I found that hummingbird tongues are composed mainly of thin cornified epithelium, lack papillae, and completely fill the internal cast of the rostral oropharyngeal cavity. Understanding this puzzle-piece match between bill and tongue will be essential for the study of intraoral transport of nectar. Likewise, I found that the structural composition and tissue architecture of the tongue groove walls provide the rostral portion of the tongue with elastic properties that are central to the study of tongue-nectar interactions during the feeding process. Detailed studies on hummingbirds set the basis for comparisons with other nectar-feeding birds and contribute to comprehend the natural solutions to collecting liquids in the most efficient way possible.